Hakikat Ilmu Pengetahuan dalam Perspektif Filsafat Pendidikan Islam: Telaah Mengenai Dikotomi Ilmu, Islamisasi Ilmu, Integrasi Ilmu, Interkoneksi Ilmu dan Implikasinya Terhadap Pengembangan Pendidikan Islam - Nurhasnah, Nurhasnah; Tiffani, Tiffani; Eldarifai, Eldarifai; Zulmuqim, Zulmuqim; Zalnur, Muhammad (Lembaga Intelektual Muda (LIM) Maluku, 2023)
As an integral part of Islamic civilization, the nature of science reflects a series of philosophical concepts, such as dichotomous science, Islamized science, integrated science, and interconnected science. The dichotomy of science raises issues related to the sharp gap between religious and worldly sciences, requiring a careful approach to overcome this disparity. Meanwhile, the Islamization of science challenges to align Islamic values with modern science, while the integration of science emphasizes the formation of a holistic framework that covers the entire spectrum of science. This writing uses a literature study method, by which the author traces the existing literature, books, books, journals, newspapers, magazines, articles, and others. The results of this writing found that overall, the implications of these problems show that the development of Islamic education requires a deep transformation in the educational paradigm, improving the quality of human resources, and forming an inclusive and holistic vision of education. Only by overcoming these problems can Islamic education play a more effective role in shaping individuals who not only excel in science, but also have a strong moral and spiritual foundation in accordance with Islamic principles